(3QSGdI aj Yde GdMSGHs - (3eLghds
(3ChdgG (B:s
(3GYde Cf GdMSGH Ydi CQHYI efGRd BMGO hYTQGJ hejFhf (B((3cPG(B) (3hCdha aGdMO dBMGO ef hGMO Edi JSYI hGdYTQGJ ef YTQGJ Edi JSYhf (B((3cPG(B) (3hGdejFhf ef eGFI Edi JSYeGFI hGdCdha ef Cda Edi JSYI BdGas
(3BNQgG (B:s
(3Ke GdBMGO aj GdYbhO Ke GdBMGO aj GdBMGO eKGdg EPG bjd dc(B: (3ce EKfG YTQ aj KdGKI YTQ? aGVQH YTQI aj YTQI Ke YTQI aj KdGKI Ke GKfjf aj KdGKI YTQI Ke GKfjf aj KdGKI Ke jLeY Pdc ajchf eGFI hSJI hNeSjf abS GdHGbj Ydi gPGs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdQjGVjGJs